Electrochemical Sensor for Propyl Gallate, Based on Synergic Effect of Gold Nanoparticle and Poly(p-aminobenzenesulfonic Acid). Issue 14 (27th October 2016) - Cyriac, Soumya T; Thomas, Divya; Vikraman, Anuja Elevathoor; Kumar, Krishnapillai Girish
Abstract : The present work reports the application of gold nanoparticle (AuNP)/poly(p-aminobenzenesulfonic acid) [poly( p -ABSA)] composite modified glassy carbon electrode (GCE) for the electrochemical determination of propyl gallate (PG). The AuNP/poly( p -ABSA) composite showed excellent electron transfer ability for the oxidation of PG by lowering the oxidation potential and remarkably enhancing the current response. Experimental parameters such as effect of pH, number of cycles of electro deposition, thickness of polymer film and scan rate were optimized. The calibration curve showed that the oxidation peak current was proportional to the concentration of PG in the range 1.0 × 10 −4 to 9.0 × 10 −6 M, with a correlation coefficient of 0.997 and limit of detection of 1.9 × 10 −7 M. Diffusion coefficient of 2.3 × 10 −6 cm 2 s −1 was calculated from chronoamperometric measurements. The designed sensor shows excellent reproducibility and stability. The developed sensor was successfully used to determine PG in edible vegetable oils and recoveries were between 98.9 and 101.3%.